Hoodlum movies : seriality and the outlaw biker film cycle, 1966-1972 - Stanfield, Peter, 1958- (Rutgers University Press, 2018)
Hoodlum Movies focuses on why and how these films were made, who they were made for, and how the cycle developed through the second half of the 1960s. Despised by critics, but welcomed by exhibitors denied first-run films, these cheaply and quickly produced movies were produced to appeal to audiences of mobile youths until 1972.